Anesthetic management of a parturient with primary pulmonary hypertension with Eisenmenger's syndrome - Kirti N Saxena; Bharti Taneja (Wolters Kluwer Medknow Publications, 2016)
Labor and delivery are associated with high mortality in parturients with primary pulmonary hypertension with Eisenmenger's syndrome. Epidural anesthesia during labor has been shown to be effective in reducing the morbidity and mortality. We administered epidural labor analgesia successfully to a parturient with primary pulmonary hypertension with Eisenmenger's syndrome. A team approach for such patients leads to successful outcome.